CT scan and Diagnostic Peritoneal Lavage: towards a better diagnosis in the area of nonoperative management of blunt abdominal trauma. Issue 9 (September 2016) - Chereau, Nathalie; Wagner, Mathilde; Tresallet, Christophe; Lucidarme, Olivier; Raux, Mathieu; Menegaux, Fabrice
Abstract: Background: The diagnosis of small bowel and mesenteric injuries (BBMI) after blunt abdominal trauma remains difficult, which results in delayed treatment and increased mortality and morbidity. Diagnostic peritoneal lavage (DPL) in patients with 1 or 2 abnormal CT findings that are suggestive of BBMI was proposed, but the rate of unnecessary surgical exploration remains high. Patients and methods: Blunt abdominal trauma patients with 1 or 2 CT findings predictive of BBMI from 2001 to 2014 underwent a DPL with calculation of a cell count ratio (CCR) dividing the ratio of white blood cells (WBCs) to red blood cells (RBCs) (WBC/RBC ratio) in the lavage fluid by the WBC/RBC ratio in peripheral blood. Surgical exploration of the abdomen was performed immediately in cases with a CCR ≥ 1. CT findings, DPL and surgery results, and global outcome were analyzed. Results: Thirty-seven were included in the study (27 males, median age of 30 years (range, 17–69 years)). Exploratory laparotomy was performed in 24 patients (65%). Sixteen patients (67%) had BBMI: 7 hollow organ perforations or tears (29%), including 4 bowel resection with primary anastomosis and 3 single sutures, and 9 patients had mesenteric injuries. CT findings associated with BBMI and hollow organ perforation were large peritoneal effusion ( p  = 0.02) and small bowel wall abnormalities ( p  = 0.002). No postoperative complications were observed. Sensitivity and specificity of DPL for the diagnosis of bowel injuries were respectively 100% (CI 95% [59–100]) and 43% (CI 95% [25–63]). The sensitivity remained 100% (CI 95% [59–100]) when the ratio was ≥4 ( n  = 10 patients), and the specificity reached 90% (CI 95% [73–98]). Conclusion: DPL is sensitive for the diagnosis of BBMI in stable trauma patients with 1 or 2 unexplained CT abnormalities, but specificity is low with a high rate of nontherapeutic laparotomy in case of CCR ≥ 1. Indications for exploratory laparotomy could be restricted to patients with a CCR ≥ 4 to improve the specificity of diagnosis management.